The burden of microplastics pollution and contending policies and regulations - Usman, Sunusi; Abdull Razis, Ahmad Faizal; Shaari, Khozirah; Azmai Amal, Mohammad Noor; Saad, Mohd Zamri; Mat Isa, Nurulfiza; Nazarudin, Muhammad Farhan (Multidisciplinary Digital Publishing Institute, 2022)
The relationship between humans and plastics has become intricate due to their versatile nature and low production cost. Plastics generation has surpassed that of other manufactured products, which, coupled with the prevailing poor waste management systems, makes it a serious problem for the terrestrial and aquatic environments as its final destination. Their extensive presence has continued to pose a significant threat, not only to the aquatic ecosystem but also to the approximately 3 billion people relying on it for their livelihood. Even more disturbing were the recent findings of these plastics in food and drinking water and the evidence of human exposure, the long-term health effects of which are largely unknown. This ubiquitous phenomenon has over time put plastics under critical observation, leading to the development of many local and international policies, resolutions, and directives aimed at addressing and reversing the menace. This review provided the first snapshot of the global and local governance strategies currently aimed at mitigating plastic pollution, their limitations, and future directions. The findings of the review revealed several aspects of microplastics (MPs) pollution to be overlooked in policy formulation, a laxity in policy implementation, and an apparent lack of indices to ascertain the impact of the regulations. Furthermore, there is currently no regulation on MPs contamination of food and drinking water and an apparent lack of funding for research into the health effects of plastics and their alternatives. This, therefore, necessitates the need for a well-coordinated approach at international and national levels to scale up these policies in all countries and translate them from paper to measurable, holistic, and realizable actions that will address all forms of plastic pollution.